The effect of tracheal stenosis on airflow using numerical modelling - Nasrul Hadi, Johari (2011)
The location and size of tracheal stenosis are among the major factors that contribute significantly to the breathing difficulties. It is crucial to understand the relationship between the two factors. Hence, this study aims to establish correlation between the location and size of the stenosis to the possibility of breathing difficulties. This work used ideal trachea model and realistic trachea model derived from Computed Tomography (CT) scan images. The stenosis was patched to the healthy trachea models at regular locations and sizes as proposed by medical practitioners. All models were then subjected to different steady breathing conditions. The changes in the flow behavior due to the different sizes and locations of the stenosis were then examined to determine the pattern of possible breathing difficulties. The results showed that, during high flow -rates, the presence of stenosis was observed to produce moderate (-150 Pa) to severe (440 Pa) pressure drop as the locations of stenosis moved closer to the bifurcation for both actual and simplified models. Two stages of pressure drop behavior also appeared consistently as the lumen became smaller at all sites. For all cases studied, significant changes in the velocity pattern were observed suggesting distorted flow rates into the bifurcation. The present simulation confirms that the overall flow behavior could be significantly affected if the size of stenosis is more than 60% for location far from the bifurcation region, and at size of 50% for location close to the bifurcation region. The outcomes of this study may help the medical practitioners and researchers to understand how dramatic increase in pressure drops occurs inside the trachea and main bronchi with the presence of stenosis at different location and size.